Performance Analysis of the 110 VDC Battery System in the DC System of the 150 kV Soppeng Substation - Koerniawan, Tony; Saputra, Fajar Sabri; Pahiyanti, Novi Gusti; Rizal, Ayu Febrina; Purwanto, Sugeng; Hasanah, Aas Wasri; Sukmajati, Sigit; Suhaevi, Evi (BEST, 2026)
Soppeng Substation is an important part of the electrical power transmission system that requires high operational reliability. One of the components that supports this reliability is the 110 VDC battery system, which functions as a backup power source for protection, control, and telecommunication equipment when the AC supply is disrupted. This study aims to analyze the feasibility of the 110 VDC battery system at the Soppeng Substation based on cell voltage, battery bank voltage, charging system performance, and the battery's ability to support DC loads. The research method includes field observations, technical measurements, and analysis of operational data collected from September to November 2025. The results show that the battery bank voltage is 119.4 V for Battery Bank 1 and 123.0 V for Battery Bank 2, with cell voltage deviations of 0.14 V and 0.18 V, respectively, which are still within the allowable limits. The rectifier output voltage ranges from 123.0–123.1 V with a current of about 6.5–6.6 A under float charging conditions. The battery capacity is able to support a DC load of 13.1 A, indicating that the battery system is feasible and reliable as a backup power source.